2022
DOI: 10.3389/fpubh.2022.861594
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Literature Review of Multi-Criteria Decision Support Methods in the Context of One Health for All-Hazards Threat Prioritization

Abstract: BackgroundMulti-Criteria Decision Analysis (MCDA) is a decision support tool that can be used in public health emergency management. The use of a One Health lens in MCDA can support the prioritization of threats and interventions which cut across the human, animal, and environmental domains. Previous literature reviews have focused on creating a snapshot of MCDA methodological trends. Our study provides an update to the MCDA methods literature with key considerations from a One Health perspective and addresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 45 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…Overall, we found that 14 literature sources gave evidence for use or utility of the frameworks or criteria to some extent, based on actual observations, a formal assessment or anecdotal evidence ( 4 , 10 , 17 , 20 , 21 , 23 , 25 , 27 , 29 32 , 39 , 40 ).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Overall, we found that 14 literature sources gave evidence for use or utility of the frameworks or criteria to some extent, based on actual observations, a formal assessment or anecdotal evidence ( 4 , 10 , 17 , 20 , 21 , 23 , 25 , 27 , 29 32 , 39 , 40 ).…”
Section: Resultsmentioning
confidence: 95%
“…The remaining nine “specific” papers had a greater focus on the prioritisation of specific public health interventions and policies and frequently cited criteria relating to “social considerations” ( n = 7), as well as “equity/fairness/ethics/equality,” “political considerations” and the “feasibility” and “cost-effectiveness” of the programmes/interventions/policies ( n = 6 each) ( 4 , 16 , 18 , 19 , 28 , 33 , 39 , 46 , 47 ). Studies categorised as “generic” ( n = 26) had a broader focus on public health interventions or multiple disease areas/risk factors ( 3 , 5 , 8 , 10 , 15 , 17 , 20 24 , 26 , 29 , 30 , 34 38 , 41 – 45 , 48 , 49 ). These studies frequently cited criteria relating to “burden of disease” ( n = 23), “health impacts of the intervention” ( n = 22), and “social considerations” ( n = 19).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations